2015
DOI: 10.1016/j.jfs.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Bank market power, factor reallocation, and aggregate growth

Abstract: a b s t r a c t Using a unique firm-level sample of approximately 700,000 firm-year observations of German small and medium-sized enterprises (SMEs), this study seeks to identify the effect of bank market power on aggregate growth components. We test for a pre-crisis sample whether bank market power spurs or hinders the reallocation of resources across informationally opaque firms. Identification relies on the dependence on external finance in each industry and the regional demarcation of regional banking mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 63 publications
0
6
0
1
Order By: Relevance
“…Zarutskie (2006) presents that banks' competition affects firm differently according to their age. Inklaar et al (2015) found that in Germany, a country with low concentration, market power stimulates growth as banks require some mark-up to generate the information needed to select the right firms to finance. 12 For further studies on the effect of financial volume on economic growth compare, for example: Loayza & Ranciere (2006) and Levine et al (2000) or, more recently, Moretti (2014) for Italy and Pascali (2014) for long-term effects.…”
mentioning
confidence: 99%
“…Zarutskie (2006) presents that banks' competition affects firm differently according to their age. Inklaar et al (2015) found that in Germany, a country with low concentration, market power stimulates growth as banks require some mark-up to generate the information needed to select the right firms to finance. 12 For further studies on the effect of financial volume on economic growth compare, for example: Loayza & Ranciere (2006) and Levine et al (2000) or, more recently, Moretti (2014) for Italy and Pascali (2014) for long-term effects.…”
mentioning
confidence: 99%
“…Specifically, we use detailed balance sheet and profit and loss data for firms that held a credit relation with a savings bank between 1995 and 2006. These data have been used before (Puri et al, 2011;Gropp et al, 2013;Behr et al, 2013;Inklaar et al, 2015) and feature an important link between savings banks and firms: the share of loans provided by savings banks (relative to total loans) SB. In comparison to the other studies, we restrict our data in two dimensions.…”
Section: Non-financial Firm Responsesmentioning
confidence: 99%
“…Si les différentiels de concurrence entre pays peuvent affecter la croissance, logiquement, les différentiels de concurrence interrégionale au sein d'une économie pourraient expliquer des dynamiques locales divergentes. Testant cette hypothèse pour l'économie allemande, qui présente la caractéristique d'avoir un marché bancaire national fragmenté, avec un fort degré d'hétérogénéité des structures bancaires d'un Länder à un autre, Inklaar et al (2015) mettent en évidence le fait que le pouvoir de marché bancaire stimule le progrès technique et la réallocation du capital vers les emplois les plus productifs. Ces résultats pour l'économie rhénane s'avèrent du reste vérifiés pour un ensemble d'économies européennes (Leroy, 2016).…”
Section: Structures Concurrentielles Et Croissance éConomiqueunclassified